Modelling of palm oil production using fuzzy expert system - ., Lily Amelia; Abdul Wahab, Dzuraidah; Hassan, Azmi (Elsevier, 2009)
The production of crude palm oil and palm kernel is a complex problem due to the influence of processing variables and environmental factors. These processing variables influence the amount of crude palm oil and palm kernel losses during processing. Instead of mathematical model, fuzzy logic approach provides a simpler and easier mechanism to describe the relationships between the processing variables and the amount of crude palm oil and palm kernel losses. In this study, four fuzzy expert system models were developed for each palm oil processing station. An approximation of centre of gravity method for defuzzification is also proposed to enable the development of the model using MicrosoftExcel. For comparison purpose, the models were also developed using MATLAB. Results obtained from the Excel model are found to be very close to the results from MATLAB.